Effectiveness and Safety of Microwave Ablation Therapy in Parathyroid Adenomas - Urfali, Furkan Ertürk; Aydin, Bünyamin; Zeren, Sezgin; Cansu, Güven Barış; Algin, Mustafa Cem; Korkmaz, Mehmet (The Arab Journal of Interventional Radiology, 2023)
Objective We report the effectiveness and safety of ultrasound (US) guided microwave ablation (MWA) treatment of parathyroid adenomas.Materials and Methods A total of 35 patients underwent US-guided MWA therapy of parathyroid adenomas. Before the procedure, blood parathyroid hormone (PTH; mean: 202.32 ± 158.46 ng/L) level, calcium (mean: 11.65 ± 0.53 mg/dL) level, and parathyroid adenoma volume (mean: 1.76 ± 0.73 cm3) were recorded. Blood parameters and US-guided follow-up evaluations were performed at 1 and 3 months after the procedure.Results Technical success was 91% for the first session. There was a statistically significant decrease in parathyroid adenoma size and calcium and PTH levels at 3 months of follow-up (p < 0.001). A perfect positive correlation (r: 0.927; p < 0.001) was found between the ablation time and the adenoma size. Transient vocal cord paralysis occurred in two (5.7%) patients and short-term (<2 hours) local pain occurred in four (11.4%) patients after the procedure.Conclusion US-guided MWA is effective in the treatment of parathyroid adenomas with low complication risk. Our preliminary results showed that MWA treatment resulted in an effective improvement in blood tests and adenoma size.
Keywords: ablation; parathyroid; ultrasound